MATHEMATICAL MODELING OF THE AMOUNTS OF TAX REVENUE RISK - Mykhailova, T. F.; Piskunova, O. V. (Science and Transport Progress, 2007)
An econometric model for forecasting volumes of tax returns and estimating risk of not being completed plan indices have been proposed.